Interim endoscopy results during neoadjuvant therapy for gastric cancer correlate with histopathological response and prognosis - Heger, Ulrike; Burian, Maria; Blank, Susanne; Bruckner, Thomas; Ott, Katja (Gastric cancer, 2014)
Background: Neoadjuvant chemotherapy for locally advanced gastric cancer leads to major histopathological response in less than 30 % of patients. Data on interim endoscopic response assessment do not exist. This exploratory prospective study evaluates early endoscopy after 50 % of the chemotherapy as predictor for later response and prognosis. Methods: Forty-seven consecutive patients were included (45 resected; 33 R0 resections). All patients received baseline endoscopy and CT scans, after 50 % of their chemotherapy (EGD-1, CT-1) and after completion of chemotherapy (EGD-2, CT-2). Interim endoscopic response (EGD-1) was assessed after having received 50 % (6 weeks) of the planned 12 weeks of neoadjuvant chemotherapy. Post-chemotherapy response was clinically assessed by a combination of CT scan (CT-2) and endoscopy (EGD-2). Histopathological response was determined by a standardized scoring system (Becker criteria). Endoscopic response was defined as a reduction of >75 % of the tumor mass. Results: Twelve patients were responders at EGD-1 and 13 at EGD-2. Nine patients (19.1 %) were clinical responders and 7 patients (15.6 %) were histopathological responders after chemotherapy. Specificity, accuracy, and negative predictive value of the interim EGD-1 for subsequent histopathological response were 31/38 (82 %), 36/47 (76 %), and 31/33 (93 %); and for recurrence or death, 28/30 (93.3 %), 38/47 (80.9 %), and 28/35 (80.0 %). Response at EGD-1 was significantly associated with histopathological response (p = 0.010), survival (p < 0.001), and recurrence-free survival (p = 0.009). Conclusions: Interim endoscopy after 6 weeks predicts response and prognosis. Therefore, tailoring treatment according to interim endoscopic assessment could be feasible, but the findings of this study should be validated in a larger patient cohort.